A MODIFIED PHILOSOPHICAL ARGUMENT FOR A BEGINNING OF THE UNIVERSE. Issue 36 (17th December 2013) - Loke, Andrew
<x content-type="archive" xml:space="preserve">Abstract</x> Craig's second philosophical argument for a beginning of the universe presupposes a dynamic theory of time, a limitation which makes the argument unacceptable for those who do not hold this theory. I argue that the argument can be modified thus: If time is beginning-less, then it would be the case that a person existing and counting as long as time exists would count an actual infinite by counting one element after another successively, but the consequent is metaphysically impossible, hence the antecedent is metaphysically impossible. I defend the premises and show that this argument does not presuppose the dynamic theory.